KORELASI DIAMETER SELUBUNG NERVUS OPTIK DAN MARSHALL CT SCORE DENGAN SKALA KOMA GLASGOW PADA CEDERA KEPALA - Rani Maria Yogipranata,* Hermina Sukmaningtyas* (NEURONA, 2018)
INTRODUCTION IN TRAUMATIC BRAIN INJURY TBI NONCONTRAST BRAIN CT SCAN IS ABLE TO DETECT AN INCREASE IN INTRACRANIAL PRESSURE WHICH IS CRUCIAL IN PATIENTS MANAGEMENT OPTIC NERVE SHEATH DIAMETERS ONSD MEASUREMENT IS A NEW METHOD THAT IS EXPECTED TO ASSESS AN INCREASE IN INTRACRANIAL PRESSURE NONINVASIVELY MARSHALL CT SCORE IS A VALID INSTRUMENT A DE FACTO STANDARD TO CLASSIFY HEAD INJURY PATIENT WHICH CORRELATES WITH AN INCREASED INTRACRANIAL PRESSURE